EFEKTIVITAS PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN PEMODELAN MATEMATIKA BERDASARKAN DISPOSISI MATEMATIS SISWA - Armelia Suryaputri; Granita Granita (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The current low level of students' mathematical modeling skills underscores the importance of implementing innovative learning models that can stimulate academic interest. This study focuses on whether the implementation of the Problem Based Learning (PBL) model can improve mathematical modeling skills when viewed based on the mathematical disposition of seventh-grade students at a State Islamic Junior High School (MTs) in Kampar. The research method applied was an experiment with a factorial design. Sampling used a cluster random sampling technique, which designated class VII.4 as the experimental group with the PBL model and class VII.2 as the control group with direct learning. Data collection was carried out through modeling ability test instruments, mathematical disposition questionnaires, and classroom activity observation sheets, which were then analyzed using a two-way ANOVA test. The findings of the data analysis showed significant differences in mathematical modeling skills between students who participated in the PBL model compared to direct learning, as well as between groups of students with high, medium, and low mathematical disposition categories. In addition, there was no interaction effect between the implementation of the PBL model and the level of disposition on students' mathematical modeling skills. The main conclusion confirms that the PBL learning model is proven to be effective in improving mathematical modeling abilities in terms of students' mathematical dispositions. ABSTRAK Rendahnya kemampuan pemodelan matematika siswa saat ini melatarbelakangi pentingnya penerapan model pembelajaran inovatif yang mampu memicu ketertarikan akademis. Penelitian ini berfokus untuk mengetahui apakah implementasi model Problem Based Learning (PBL) dapat meningkatkan kemampuan pemodelan matematika jika ditinjau berdasarkan disposisi matematis siswa kelas VII di salah satu MTs Negeri di Kampar. Metode riset yang diterapkan adalah eksperimen dengan desain faktorial. Penarikan sampel menggunakan teknik cluster random sampling, yang menetapkan kelas VII.4 sebagai kelompok eksperimen dengan model PBL dan kelas VII.2 sebagai kelompok kontrol dengan pembelajaran langsung. Pengumpulan data dilakukan melalui instrumen tes kemampuan pemodelan, angket disposisi matematis, serta lembar observasi aktivitas kelas, yang kemudian dianalisis menggunakan uji anova dua arah. Temuan analisis data menunjukkan adanya perbedaan signifikan pada kemampuan pemodelan matematika antara siswa yang mengikuti model PBL dibandingkan dengan pembelajaran langsung, serta antara kelompok siswa berkategori disposisi matematis tinggi, sedang, dan rendah. Selain itu, ditemukan tidak terdapat efek interaksi antara penerapan model PBL dan tingkat disposisi terhadap kemampuan pemodelan matematika siswa. Kesimpulan utama menegaskan bahwa model pembelajaran PBL terbukti efektif meningkatkan kemampuan pemodelan matematika ditinjau dari disposisi matematis siswa.